An ethical intuitionist account of transparency of algorithms and its gradations - Paul Hayes (Business Research, 2020)
To make evaluations about the morally relevant impacts of algorithms, transparency is needed. This paper lays out discussion of algorithms and transparency in an explicitly moral analysis with a special focus on the domain of justice and security. The paper provides an account of the moral import of transparency, defined itself as an instrumental value denoting a state of affairs conducive to acquisition of knowledge about some X. A normative account of transparency is outlined relying on an intuitionist framework rooted in the works of Ross and Robert Audi. It will be argued that transparency can be derived as a subsidiary (prima facie) principle from other duties including beneficence and justice and that it is groundable in the value of knowledge. Building on this foundation, the paper examines transparency and duty conflict with a special focus on algorithms in justice and security, recognising that complete transparency can be impossible where duties conflict. It is argued that as a subsidiary (prima facie) principle, transparency is overridable but ineradicable, which is to say that sufficiently justifiable reasons for secrecy or opacity can licence limiting transparency, that is, there may be occasion where full transparency is not our final duty.
Keywords: 650; Values; Algorithms; Intuitionism; Transparency; Justice and security